Analisis Faktor-Faktor Penghambat Perkembangan Koperasi Simpan Pinjam Pembiayaan Syariah Nur Hayyu Ambara - Hafazah, Hikmatul (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2023)
At this time, various types of cooperatives have grown and developed, both single-purpose and multi-purpose. The business activities of these cooperatives are in the fields of credit, industry, trade, agriculture, consumption. syariah nur hayyu ambara, the method used is quality, with purposive sampling, data analysis techniques using the adoption of theories from miles and hubarman. The results of the study show that the factors that hinder the development of the Nur Hayyu Ambara Sharia Savings and Loans Cooperative (KSPPS) Nur Hayyu Ambara in 2021 are low member participation and management performance. Member participation can be seen from selling products, buying products, using services, paying principal savings, mandatory savings and even voluntary savings have not been fully utilized or used by members, while the performance of the management can be seen from the lack of active management in opening cooperatives, the ability of the management to attract members, the ability of the management to operate equipment and the ability of management to generate high profits/ SHU at the Nur Hayyu Ambara Savings and Loans and Sharia Financing Cooperative (KSPPS). So that the existence of obstacles to the development of this cooperative will certainly affect the development of cooperatives from time to time even the Nur Hayyu Ambara Savings and Loans and Sharia Financing Cooperative (KSPPS) cannot develop compared to other cooperatives.